Characteristics of soil microbial phospholipid fatty acids in artificial, black-soil mountain degraded, and natural grasslands in the source region of the Three Rivers - Xie, Lele; Ma, Yushou; Wang, Yanlong; Ma, Yuan; Wang, Xiaoli; Liu, Ying (PeerJ, 2025)
Background The source region of the Three Rivers is a concentrated distribution area of alpine grassland. Due to intensified human interference and unsustainable land use, the vegetation and soil in these grasslands have undergone severe degradation, resulting in extensive areas of secondary bare land known as “black soil beach”. A specific form of this degradation is referred to as “black-soil mountain”. To address soil degradation in this region, the establishment of artificial grassland has been proposed. Recent research on grassland restoration has increasingly focused on belowground processes, particularly the role of soil microbial communities in soil recovery. Methods This study quantitatively analyzed vegetation characteristics, soil nutrients, microbial community structure, and influencing factors across three grassland types: artificial grassland (AG), black-soil mountain degraded grassland (BG), and natural grassland (NG). Standard laboratory analyses and the phospholipid fatty acid (PLFA) method were employed. Results The establishment of artificial grassland significantly increased aboveground biomass and the contents of soil organic carbon, total nitrogen, and total phosphorus, while notably reducing species richness. A total of 29 PLFA biomarkers were detected across the three grassland types, with AG showing significantly higher biomarker content than BG and NG. Key PLFA biomarkers included 16:1 w7c, 18:1 w7c, 15:0 iso, 15:0 anteiso, 16:00, and 18:1 w9c. Among microbial groups, bacteria were most abundant, followed by fungi, actinomycetes (act), and arbuscular mycorrhizal fungi (AMF). Compared to BG, AG exhibited significantly lower G+/G−and saturated-to-monounsaturated fatty acid (Sat:mono) ratios. Correlation analysis revealed that total PLFA, bacterial (B), fungal (F), G+, and G−contents were significantly or highly significantly positively correlated with soil organic carbon, total nitrogen, and water content (P < 0.01; P < 0.001). Redundancy analysis (RDA) showed that two principal components explained 76.96% and 13.74% of the variation in microbial community structure, with soil organic carbon and total nitrogen identified as the main driving factors. Conclusion The establishment of artificial grassland is an effective strategy for restoring black-soil mountain degraded grassland. Monitoring microbial PLFA diversity and composition provides a reliable index for assessing soil environmental changes and nutrient dynamics. However, even after five years of restoration, the soil functionality of artificial grassland does not fully recover to the level of natural grassland.
Keywords: Artificial grassland; PLFA; Soil microbial community; Soil nutrients; Source region of sanjiangyuan